Possible role of rainfall in the epidemiology of tick-borne encephalitis - Danielová, V; Benes, C (Central European journal of public health, 1997)
The assumption that the amount of rainfall in the summer months influences the frequency of TBE is based on the fact that the determining factor for the existence, development and activity of Ixodes ricinus is relative air humidity (RH) and the finding that low RH negatively influences dynamics of infection and infection rate of I. ricinus with TBE virus. A higher incidence of TBE then develops due to the coincidence of increased activity of ticks and recreational activity of humans after an intense prolonged rainfall. This presumption was verified by comparing the dynamics of rainfall as an indicator of RH in the tick environment with concomitant seasonal fluctuations of TBE incidence in humans. The total monthly rainfall in two regions of the Czech Republic was compared with data on the incidence of TBE in each respective region and period. Furthermore, in the district of Ceské Budĕjovice, typical by high prevalence of this disease, a detailed follow-up was carried out by decades. The comparisons were made between April and October from 1993 to 1995. The values of both variables were related to their long-term averages estimated within each particular period and region. Monthly data were analyzed for the Central Bohemian Region and the South Bohemian Region, both with a high incidence of TBE. The July above-average incidence of TBE was preceded by an above-average rainfall in June. If there was a below-average rainfall, there was a below-average incidence of TBE afterwards. Whenever, there was an above-average rainfall in August then there was an above average incidence of TBE in September, in the opposite case, no September peak of TBE occurred. The follow-up at ten-day intervals shows that any above-average rainfall was followed by an increased incidence of TBE, in every other ten-day period or two. This time shift is due to the incubation period, and partly also to the scattered attacks by ticks during the period of increased RH. The relationship found could be useful for the short-term prognosis of TBE incidence as well as for individual prevention of this serious infection by taking special care when going outdoors after heavy rain.
Keywords: Seasons; Humidity; Prevalence; Rain; Population Surveillance; volnočasové aktivity; Ixodes; Incidence; Česká republika; Encephalitis, Tick-Borne; déšť; prevalence; incidence; Czech Republic; surveillance populace; Follow-Up Studies; klíšťová encefalitida; následné studie; zvířata; vlhkost; Humans; klíště; Leisure Activities; roční období; lidé; Animals